2021
DOI: 10.3390/jcm10173890
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Function Following Anthracycline-Based Chemotherapy in Patients with Breast Cancer without Previous Cardiac Disease—A Meta-Analysis

Abstract: Background: Anthracycline-based chemotherapy (ANT) remains among the most effective therapies for breast cancer. Cardiotoxicity from ANT represents a severe adverse event and may predominantly manifest as heart failure. While it is well-recognised that left ventricular systolic heart failure assessment is key in ANT-treated patients, less is known about the relevance of LV diastolic functional impairment and its characterisation. Methods: Studies reporting on echocardiographic diastolic function parameters bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
0
6
0
2
Order By: Relevance
“…The diastolic dysfunction was shown to occur as early as 2 days after Dox injection in a rat model [ 65 ]. However, a recent meta-analysis showed that anthracycline-chemotherapy in breast cancer patients without previous cardiac disease had a modest early impact on E/A and E/E’ ratios [ 66 ]. Increased levels of left ventricular fibrosis as early as 3 days after Dox treatment in our previous studies [ 3 ] warrant further studies on the impact of Dox on diastolic function by measuring mitral valve inflow patterns and tissue doppler velocities at the lateral annulus of the mitral valve.…”
Section: Discussionmentioning
confidence: 99%
“…The diastolic dysfunction was shown to occur as early as 2 days after Dox injection in a rat model [ 65 ]. However, a recent meta-analysis showed that anthracycline-chemotherapy in breast cancer patients without previous cardiac disease had a modest early impact on E/A and E/E’ ratios [ 66 ]. Increased levels of left ventricular fibrosis as early as 3 days after Dox treatment in our previous studies [ 3 ] warrant further studies on the impact of Dox on diastolic function by measuring mitral valve inflow patterns and tissue doppler velocities at the lateral annulus of the mitral valve.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous work, data indicated a cohort of premenopausal women diagnosed with hormone receptor-positive breast cancer undergoing near-complete estrogen deprivation therapy exhibited short-term increases in global longitudinal and radial modulus values of 40%, which was significantly greater than changes in elasticity in a comparator cohort of premenopausal patients. We also expect changes in stiffness due to anthracycline therapy to be larger with evidence showing significant myocardial stiffness modulation due to chemotherapies, 34 indicating our methodology is capable of indicating changes in LV stiffness as a results of cardiotoxic antineoplastic therapies. Our results also define a threshold of significance to differentiate biological changes in modulus from methodological variability, important for potential future clinical implementation when assessing individual elasticity measurements.…”
Section: Discussionmentioning
confidence: 92%
“…Mincu et al used echocardiography to detect heart failure. The evaluation of left ventricular systolic heart failure is recognized as the key to treating patients; thus, Mincu specifically evaluates left ventricular diastolic dysfunction [ 34 ]. The pulse wave in this study was mainly used to evaluate the traditional left ventricular contractility.…”
Section: Discussionmentioning
confidence: 99%